Development of a tool for preliminary calculations of performance and loads on a wind turbine rotor, and utilization of this tool to achieve a rotor-strength-optimized power curve. - Rune Pedersen (2012)
In a time where the wind turbine industry draws ever closer of reaching the goal of developing a floating offshore wind turbine, capable of operating far away from the coastline, new possibilities might open in terms of controlling the energy production of wind turbines. Because of the absence of human presence at such a location, the current restrictions laid upon the industry to limit the implications on humans in the form of noise would most likely be revoked. This in turn would make it possible to develop new philosophies of mating rotor and generator, so that the higher wind speeds ranges could be exploited to a higher degree than today. This work will investigate how much reserve of solidity an existing horizontal axis wind turbine rotor, equipped with an variable pitch system, has at wind speeds above its reference value. To do this, a computational tool for calculating preliminary results of performance and loads on such a rotor will be developed, so that the results of different wind speeds and power settings can be compared to the results of the reference wind speed and power output. Utilizing this tool, it will further be strived to develop an improved power curve, from an energy point of view, with the rotor strength as the limiting factor.